Dynamical systems in computational psychiatry: A toy-model to apprehend the dynamics of psychiatric symptoms - Gauld, Christophe; Depannemaecker, Damien (Frontiers in Psychology, 2023)
These last years, scientific research focuses on the dynamical aspects of psychiatric disorders and their clinical significance. In this article, we proposed a theoretical framework formalized as a generic mathematical model capturing the heterogeneous individual evolutions of psychiatric symptoms. The first goal of this computational model based on differential equations is to illustrate the nonlinear dynamics of psychiatric symptoms. It offers an original approach to non-linear dynamics to clinical psychiatrists. Thus, we propose a 3+1 dimensions model (x, y, z + f) reproducing the clinical observations encountered in clinical psychiatry with: a variable modeling environmental noise (z) on the patient’s internal factors (y) with its temporal specificities (f) and symptomatology (x).